And the winner is ... Galway: a cultural anatomy of a winning designate. Issue 5 (28th July 2020) - Collins, Patrick
ABSTRACT: The following is a cultural anatomy of the city of Galway in the west of Ireland. The paper traces the evolution of the cultural profile of the city over the past four decades. It places the city's recent success regarding international accolades in the context of the creative city script. This work sets out to explore how the city, once famed for its cultural producers, has evolved into a site for cultural consumption; an evolution of a city of culture making to culture taking. Reference is also made to how local government has branded the city as a creative one by targeting cultural designations (such as UNESCO Creative City; European Capital of Culture). The purpose of the paper is to situate Galway's cultural anatomy in the broader context of neoliberal urbanism, one that takes culture as ancillary amenity to attract tourists and investors. The paper finishes by positing a future path for a sustainable development for the creative/cultural sector and the city more broadly.